The whispering road - Michael, Livi, 1960- (London : Puffin Books, 2006)
In Victorian England, poverty-stricken, orphaned siblings Joe and Annie escape from the abusive farmer they work for and try to survive in Manchester, with help from a friendly tramp, a mysterious dog-woman, and a renegade printer who supports the rights of the poor.
Book Links (A.L.A.)
Booklist
School Library Journal
4.9
5-8
5-8
Keywords: Brothers and sisters -- Juvenile fiction; Child labor -- Great Britain -- History -- Victoria, 1837-1901 -- Juvenile fiction; City and town life -- Fiction; Orphans -- Juvenile fiction; Poverty -- Great Britain -- History -- Victoria, 1837-1901 -- Juvenile fiction; Supernatural -- Juvenile fiction; Brothers and sisters -- Fiction; Child labor -- Fiction; City and town life -- Fiction; Historical fiction; Orphans -- Fiction; Poverty -- Fiction; Supernatural -- Fiction; Child labor -- Fiction; City and town life -- Fiction; Historical fiction; Occult fiction; Orphans -- Fiction; Poverty -- Fiction; Siblings -- Fiction; Supernatural -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Juvenile fiction; Manchester (England) -- History -- 19th century -- Juvenile fiction; Great Britain -- History -- Fiction; Manchester (England) -- History -- Fiction; Great Britain -- History -- 19th century -- Fiction; Manchester (England) -- History -- Fiction